March 2021 Update to the Global Database of Shared Prosperity : What’s New - Yang, Judy; Nguyen, Minh Cong (World Bank, Washington, DC, 2021)
Shared prosperity is the World Bank’s second Twin Goal, introduced in 2013. It is defined as the growth in household per capita income or consumption of the poorest 40 percent of the population. The Global Database of Shared Prosperity (GDSP) is the database that is used to monitor progress of this indicator. The March 2021 update introduces the 8th edition of the Global Database of Shared Prosperity. This note documents the data availability in this edition and the main differences with the 7th edition.